Time to Diagnose Endometriosis: Current Status, Challenges and Regional Characteristics—A Systematic Literature Review - De Corte, Pauline; Klinghardt, Moritz; von Stockum, Sophia; Heinemann, Klaas (BJOG : an international journal of obstetrics and gynaecology, 2025)
ABSTRACT Background Endometriosis diagnosis reportedly faces delays of up to 10 years. Despite growing awareness and improved guidelines, information on the current status is limited. Objectives To systematically assess the published evidence on the status of time to diagnosis in individuals with endometriosis, with respect to the definition of time to diagnosis, geographical location and patient characteristics. Search Strategy MEDLINE (via PubMed) and Embase were searched for publications reporting time to diagnosing endometriosis since 2018. No restrictions to population or comparators were applied. All publications were screened by two independent reviewers. Selection Criteria Search results were limited to primary publications of randomised controlled trials, non‐randomised trials and observational studies. Case reports, secondary publications and grey literature were excluded. No restrictions were made regarding language, provided that an English title and were available. Data Collection and Analysis Publications were assessed with respect to time to diagnosis, diagnostic methods, study type, study country and potential bias. Main Results The 17 publications eligible for inclusion in this literature review were all observational studies. The publications reported diagnosis times between 0.3 and 12 years, with variations depending on the definition of time to diagnosis (overall, primary, or clinical), geographical location and characteristics of the included study population. Evidence was of poor to good quality overall. Conclusions Diagnostic delay is still present, primarily driven by physicians, and this review underscores the need for standardised definitions, increased awareness and targeted diagnostic interventions.